214k views
3 votes
Solve the equation using the Zero-Product Property.

(3x-6)(5x+3)=0

a. 2, 3/5
b. -2, -3/5
c. 2, -3/5
d. -3, 5

1 Answer

1 vote

Answer:

Option (b) is correct.

Using the Zero-Product Property, on the given equation
(3x-6)(5x+3)=0 we get,
x=2 and
x=(-3)/(5)

Explanation:

Consider the given equation ,
(3x-6)(5x+3)=0

Zero- product property states that if the product of two term is zero then either first term is zero or second term is zero

That is
p.q=0 \Rightarrow p=0\ \text{or} \ q=0

Consider the given equation ,
(3x-6)(5x+3)=0

Applying zero-product property, we get,


(3x-6)(5x+3)=0

this implies that either
(3x-6)=0 or
(5x+3)=0

either
x=2 or
x=(-3)/(5)

Thus, using the Zero-Product Property, on the given equation
(3x-6)(5x+3)=0 we get,
x=2 and
x=(-3)/(5).


User Vasaka
by
5.3k points